Munasabat: Satu Bahagian dari Pengajian Al-Qur'an - Hj. Yusoff, Zulkifli (Jurnal Usuluddin, 1995)
The article concentrates on the 'Ilm al-Munasabat which is found in the Qur'an, such as the link between a verse to another, as well as a Surah to a Surah. The author complements his writing by bring in several relevant stories.